Hypoxia and Alpha-Synuclein: Inextricable Link Underlying the Pathologic Progression of Parkinson's Disease - Guo, Mengyuan; Ji, Xunming; Liu, Jia (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease, with typical motor symptoms as the main clinical manifestations. At present, there are about 10 million patients with PD in the world, and its comorbidities and complications are numerous and incurable. Therefore, it is particularly important to explore the pathogenesis of PD and find possible therapeutic targets. Because the etiology of PD is complex, involving genes, environment, and aging, finding common factors is the key to identifying intervention targets. Hypoxia is ubiquitous in the natural environment and disease states, and it is considered to be closely related to the etiology of PD. Despite research showing that hypoxia increases the expression and aggregation of alpha-synuclein (α-syn), the most important pathogenic protein, there is still a lack of systematic studies on the role of hypoxia in α-syn pathology and PD pathogenesis. Considering that hypoxia is inextricably linked with various causes of PD, hypoxia may be a co-participant in many aspects of the PD pathologic process. In this review, we describe the risk factors for PD, and we discuss the possible role of hypoxia in inducing PD pathology by these risk factors. Furthermore, we attribute the pathological changes caused by PD etiology to oxygen uptake disorder and oxygen utilization disorder, thus emphasizing the possibility of hypoxia as a critical link in initiating or promoting α-syn pathology and PD pathogenesis. Our study provides novel insight for exploring the pathogenesis and therapeutic targets of PD.